2002
DOI: 10.1021/jp020708v
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and Optimality of Light Harvesting in Cyanobacterial Photosystem I

Abstract: As most biological species, photosynthetic lifeforms have evolved to function optimally, despite thermal disorder and with fault tolerance. It remains a challenge to understand how this is achieved. To address this challenge the function of the protein-pigment complex photosystem I (PSI) of the cyanobacterium Synechococcus elongatus is investigated theoretically. The recently obtained high resolution structure of this complex exhibits an aggregate of 96 chlorophylls that are electronically coupled to function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
252
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(269 citation statements)
references
References 55 publications
16
252
1
Order By: Relevance
“…where N Chl ¼ 96 is the number of chlorophylls in one monomer (Sener et al, 2004;Damjanović et al, 2002;Sener et al, 2002) . Figure 4A illustrates the couplings V MN;mn across the five monomers, I, II, III, II', and III', as labeled in Figure 4B.…”
Section: Computational Model Of the Psi Membrane Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…where N Chl ¼ 96 is the number of chlorophylls in one monomer (Sener et al, 2004;Damjanović et al, 2002;Sener et al, 2002) . Figure 4A illustrates the couplings V MN;mn across the five monomers, I, II, III, II', and III', as labeled in Figure 4B.…”
Section: Computational Model Of the Psi Membrane Regionmentioning
confidence: 99%
“…The cross-monomer trapping probabilities p M;m;N describe the level of excitation sharing between neighboring monomers and are plotted in Figure 4C for the reference monomer N ¼ I. The cross-trapping probabilities averaged over each monomer Figure 3) does not provide a significant improvement of quantum yield (Supplemental Figure 7E) over that of an isolated trimer (Sener et al, 2002) due to the short trapping time of PSI. Since the quantum yields for the observed trimer array ( Figure 3) and for isolated trimers are nearly identical, the primary role of the trimer packing pattern appears to maximize the packing efficiency of PSI complexes in the membrane rather than to facilitate intertrimer energy transfer.…”
Section: Computational Model Of the Psi Membrane Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,20,21,27,28 The effect of removing a chromophore on EET efficiency has also been investigated, and it has been suggested that photosynthetic EET networks display a robustness to the loss of a chromophore in the network through the utilisation of multiple EET pathways. 6,[29][30][31][32] In contrast to these previous investigations, which have focussed on the role of site energy fluctuations, environmental fluctuations, and exciton trapping rates, this article focusses predominantly on evaluating how the electronic Hamiltonian of the EET system governs the robustness and optimal EET characteristics of a biological photosynthetic system. Specifically, we adopt a network-based view of photosynthetic EET systems and focus on investigating quantum transport dynamics in a prototypical PPC, the FMO complex.…”
Section: Introductionmentioning
confidence: 99%
“…We build the transition matrix K xy by using the inter-chlorophyll excitation transfer rates that were calculated in Ref. [22] based on the theory developed in [23] and the recently obtained structure of photosystem I [24]. The MFPT τ x from chlorophyll x to the P700 pair is then [20] …”
mentioning
confidence: 99%